Targeting top terrorists: understanding leadership removal in counterterrorism strategy - Price, Bryan C. (Columbia studies in terrorism and irregular warfare, 2019)
Bryan C. Price offers a data-driven examination of leadership decapitation tactics in counterterrorism. Analyzing hundreds of cases of leadership turnover from over two hundred terrorist groups, Price demonstrates that the loss of top leaders significantly reduces terror groups’ life spans.